Incidence of arthritis and its treatment trials in cattle - Durmus, AS; Han, MC (Indian Veterinary Journal, 2004)
Arthritis particulary affecting calves at the first 3 months of the life is a significant problem, which needs care and attention. Schedule of treatment for successful management is detailed.
Keywords: Disorders; Digit